Smartphones for Law Students – Persuasive, Pervasive and Legal: a Research Study. (12th September 2014) - Abbas, Zaki; MacFarlane, Andrew; Göker, Ayşe
Abstract Smartphones have quickly become a key part of our daily lives. Over 70 percent of people in the UK own such a device and law students are no exception to this far-reaching trend1. The use of these devices has posed some significant questions on the extent of their impact on information seeking behaviour and in relation to information delivery of resources. Zaki Abbas, Andrew MacFarlane and Ayşe Göker, who have recently begun a research project together, seek to not only examine the information seeking behaviours (ISBs) of law students using their Smartphones for academic information retrieval, but also to investigate perspectives from subject law librarians from Higher Education Institutions (HEIs) throughout the UK. There is an impression that students tend to find Smartphones more appealing for their information seeking needs compared to the professional resources and services, such as virtual libraries, which their HEI have already invested in. The result leads to a deep concern from subject librarians that students may be at risk from weakening research skills as well as relying too much on poor information sources not specifically designed to meet their information needs within the academic context5. The authors also suggest that information service providers to be more pro-active in providing information to students through more user-friendly interfaces as well as capitalise on the growing use of the Smartphone as a means to deliver their product4, 5, 6, 15.